Laparoscopic surgery and coronavirus disease: What do we know now? (Clinics, 2020)
Questions regarding the transmissibility of the novel coronavirus disease (COVID-19) remain unanswered. It is known that the transmission of the severe acute respiratory syndrome coronavirus (SARS-CoV) occurs predominantly through droplets and contact. However, aerosols can be generated in some situations, such as orotracheal intubation, ventilation, and the use of electric or ultrasonic scalpels, and can therefore potentially contaminate the care team if adequate protection is not used. It is therefore necessary to assess issues of transmissibility of COVID-19 during surgery in infected patients. This review gathers the recent research pertaining to this topic. A search of the literature was performed using the PubMed and UpToDate databases with the search terms ‘‘surgery’’ and ‘‘covid-2019,’’ in addition to other MeSH variants of these terms. We do not have consistent evidence on the exposure of healthcare professionals assisting patients with COVID-19 undergoing laparoscopy or the impact of such exposure. In view of the evidence obtained and drawing parallels with other infectious and contagious diseases, medical personnel must wear complete protective attire for proper protection against the generated aerosol. Further studies are required to assess the impact of such surgeries on healthcare professionals conducing or assisting with these procedures.